ANALISIS PERAN AKUNTANSI MANAJERIAL DALAM MENINGKATKAN EFEKTIVITAS PENGAMBILAN KEPUTUSAN MANAJEMEN - Chorrina Clarra Br Meliala; Theresia Mika Kesia Sitorus; Novianti Hutagalung; Veronica D Hutagalung (POLITEKNIK LP3I JAKARTA, 2026)
Managerial accounting plays a crucial role in providing relevant, accurate, and timely information to support management decision-making processes. This study aims to analyze the role of managerial accounting in enhancing the effectiveness of management decision-making within companies. The research employs a qualitative descriptive approach, utilizing data collection techniques that involve a literature review and the analysis of various scholarly sources regarding managerial accounting practices and managerial decisions. The findings indicate that the implementation of managerial accounting assists management in the processes of planning, controlling, and evaluating organizational performance. Cost information, budget analysis, and performance reports generated through managerial accounting contribute to reducing uncertainty and improving the quality of both strategic and operational decisions. Furthermore, the use of effective managerial accounting information systems can enhance organizational efficiency and corporate competitiveness within a dynamic business environment. This study demonstrates that managerial accounting plays a significant role in improving the effectiveness of management decision-making by providing relevant information that supports the achievement of organizational goals.